Perinatal exposure to the fungicide ketoconazole alters hypothalamic control of puberty in female rats - Franssen, Delphine; Johansson, Hanna K. L.; Lopez-Rodriguez, David; Lavergne, Arnaud; Terwagne, Quentin; Boberg, Julie; Christiansen, Sofie; Svingen, Terje; Parent, Anne-Simone (Frontiers in Endocrinology, 2023)
Estrogenic endocrine disrupting chemicals (EDCs) such as diethylstilbestrol (DES) are known to alter the timing of puberty onset and reproductive function in females. Accumulating evidence suggests that steroid synthesis inhibitors such as ketoconazole (KTZ) or phthalates may also affect female reproductive health, however their mode of action is poorly understood. Because hypothalamic activity is very sensitive to sex steroids, we aimed at determining whether and how EDCs with different mode of action can alter the hypothalamic transcriptome and GnRH release in female rats. Female rats were exposed to KTZ or DES during perinatal (DES 3-6-12µg/kg.d; KTZ 3-6-12mg/kg.d), pubertal or adult periods (DES 3-12-48µg/kg.d; KTZ 3-12-48mg/kg.d). Ex vivo study of GnRH pulsatility revealed that perinatal exposure to the highest doses of KTZ and DES delayed maturation of GnRH secretion before puberty, whereas pubertal or adult exposure had no effect on GnRH pulsatility. Hypothalamic transcriptome, studied by RNAsequencing in the preoptic area and in the mediobasal hypothalamus, was found to be very sensitive to perinatal exposure to all doses of KTZ before puberty with effects persisting until adulthood. Bioinformatic analysis with Ingenuity Pathway Analysis predicted “Creb signaling in Neurons” and “IGF-1 signaling” among the most downregulated pathways by all doses of KTZ and DES before puberty, and “PPARγ” as a common upstream regulator driving gene expression changes. Deeper screening of RNAseq datasets indicated that a high number of genes regulating the activity of the extrinsic GnRH pulse generator were consistently affected by all the doses of DES and KTZ before puberty. Several, including MKRN3, DNMT3 or Cbx7, showed similar alterations in expression at adulthood. In conclusion, GnRH secretion and the hypothalamic transcriptome are highly sensitive to perinatal exposure to both DES and KTZ. The identified pathways should be explored further to identify biomarkers for future testing strategies for EDC identification and when enhancing the current standard information requirements in regulation.